Electric steelmaking dust as a raw material for coagulant production - Svetlana V. Sverguzova; Zhanna A. Sapronova; Olga S. Zubkova; Anastasia V. Svyatchenko; Karina I. Shaikhieva; Yulia S. Voronina (Записки Горного института, 2023)
The paper describes the issues associated with waste generated during steel production and processing, in particular the dust from electric arc furnaces (EAF). An effective solution for the disposal of such waste is its involvement in processing to obtain valuable products. This paper studies the physical and chemical properties of EAF dust produced during the smelting of metallized pellets and captured by the dust and gas cleaning system of the steel-smelting shop at the Oskol Electrometallurgical Combine, Belgorod Region. The results obtained in the study of the chemical and disperse compositions of dust, the microstructure of the surface made it possible to propose the use of dust as a raw material for coagulant production. The conditions of acid-thermal treatment of dust are determined, contributing to the partial dissolution of iron (II), (III), and aluminium compounds, which ensure the coagulation processes during wastewater treatment. Model solutions show high efficiency (> 95 %) of water treatment from heavy metal ions by modified EAF dust.